1993
DOI: 10.1071/rd9930039
|View full text |Cite
|
Sign up to set email alerts
|

Supersensitivity to the stimulant action of noradrenaline on human myometrium near term

Abstract: Noradrenaline (10-50 nM) and tyramine (0.05-1 mM) enhanced contractile force elicited by field stimulation of strips of myometrium from non-pregnant and pregnant women. In higher concentrations, noradrenaline produced sustained contractions. The EC50 values for noradrenaline were 0.4 microM in tissues from pregnant women and 3.1 microM in tissues from non-pregnant women; maximum responses were greater in the former tissues. In addition, the effects of noradrenaline on myometrium from pregnant women were more m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In contrast, the same study in the presence of WB4101 demonstrated an increased proportion (+ 63%) of the alB subtype in the high affinity agonist state. So, it is conceivable to assume that the atIB-subtype may account for the supersensitivity of the myometrium to the stimulating action of norepinephrine at the end of pregnancy in rats and humans [1,31]. This idea is also supported by the fact that the G-coupled state of aOB-adrenergic receptor is increased at term concomitantly with a norepinephrine release from the uterine sympathetic nerves [32] and a significant enhancement of Gatq subunit [24,33].…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the same study in the presence of WB4101 demonstrated an increased proportion (+ 63%) of the alB subtype in the high affinity agonist state. So, it is conceivable to assume that the atIB-subtype may account for the supersensitivity of the myometrium to the stimulating action of norepinephrine at the end of pregnancy in rats and humans [1,31]. This idea is also supported by the fact that the G-coupled state of aOB-adrenergic receptor is increased at term concomitantly with a norepinephrine release from the uterine sympathetic nerves [32] and a significant enhancement of Gatq subunit [24,33].…”
Section: Discussionmentioning
confidence: 94%
“…This could be the consequence of the decline in P concentration (Table 1) during the last days of pregnancy. Since it has been established that Gqa stimulates phosphoinositide-specific phospholipase C, its increment may account in part for the supersensitivity of the myometrium to the contractile effects of oxytocin [47] and norepinephrine [5,48] in relation with an increased number of oxytocin [41,49] and al-adrenergic receptors [50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, progesterone has been shown to stabilize the high affinity state of the receptor, thus increasing the coupling of the 2 -ARs to adenylyl cyclase (Cohen-Tannoudji et al 1991) and facilitating uterine quiescence. In contrast, the 1 -ARs play an important role in the mechanism of parturition, as supported by several lines of evidence (Legrand & Maltier 1986, Pennefather et al 1993. At delivery, myometrial contractions are initiated primarily by a rise of intracellular Ca 2+ .…”
Section: Introductionmentioning
confidence: 94%